Recent Mediterranean Outflow Water and Atlantic Meridional Overturning Circulation correlations - Mosquera-Giménez, Ángela; Vélez-Belchí, Pedro (2019)
The Atlantic Meridional Overturning Circulation (AMOC) is the main contributor to the heat interchange in the North Atlantic, carrying around 1.5 PW at 25°N, which helps to regulate the climate, especially in Europe. Any slowdown of the AMOC would produce an important decrease in the temperature in the regions around the North Atlantic and also in other parts of the world. A factor that affects the strength of the AMOC is the input of water. While an input of freshwater would produce a reduction in the transport of the AMOC, a supply of salty water, such as the Mediterranean Outflow Water (MOW), would enhance the formation of deep water, strengthening the AMOC, and even stabilizing it. The aim of this work is to determine if the variation of the volume of the MOW is having any effect in the fluctuation of the transport of the AMOC. In order to achieve this, we developed a method to estimate the volume of MOW in the North Atlantic using the Roemmich-Gilson Argo Climatology and compared it with the observations of the AMOC from the RAPID array. Although statistically, there was a low correlation, the similarities between the MOW and RAPID time series were evident, especially for the period 2012-2017. A possible explanation of this resemblance is that the changes that occur in the AMOC also affect the interchange between the Atlantic and the Mediterranean, and therefore the volume of MOW in the Atlantic.